Lithium / sodium-loving current collector for lithium / sodium metal battery and preparation method and application of lithium / sodium-loving current collector

By designing the lithium/sodium layer on the collector of lithium/sodium metal batteries, the degradable wood cellulose material is used to solve the problem of uncontrollable growth in the growth of the Zhi crystal, realizing the uniform deposition and battery safety of lithium/sodium, and the safety of battery safety. Improvement, while reducing pollution to the environment.

CN119381458APending Publication Date: 2025-01-28HEFEI UNIV OF TECH

Patent Information

Application Number
CN202411496712.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Existing lithium/sodium metal batteries face interface problems and safety problems caused by uncontrollable dendrites' growth, and traditional current collector materials are not degradable, and the use of organic solvents poses a threat to the environment and health.

Method used

Naturally degradable woody cellulose is used as the raw material of the collector. The lithium/sodium layer is designed on the copper foil or aluminum foil through the deodorization of the ion, and the lithium is regulated to regulate the lithium/sodium chin crystal.

Benefits of technology

The uniform deposition of lithium/sodium is achieved, effectively suppressing the growth of lithium/sodium chopry, reducing hidden dangers of the battery, and avoiding the use of organic solvents and reducing pollution to the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381458A_ABST
    Figure CN119381458A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium / sodium-loving current collector for a lithium / sodium metal battery and a preparation method and application thereof. The lithium / sodium-loving current collector comprises a current collector substrate (copper foil or aluminum foil) and a lignocellulose-based lithium / sodium-loving layer loaded on the surface of the current collector substrate. When the lithium / sodium-philic current collector is used in a lithium / sodium metal battery, a relatively good homogenization effect can be achieved on deposition of lithium / sodium, growth of lithium / sodium dendrites is effectively inhibited, potential safety hazards of the battery are greatly reduced, and the raw materials used in the lithium / sodium-philic current collector are relatively rich in resources, low in price, biodegradable and relatively environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy storage batteries, and in particular to a lithium / sodium-philic current collector for lithium / sodium metal batteries and a preparation method and application thereof. Background Art

[0002] Since the energy density of lithium / sodium ion batteries has been developed to the limit, it is difficult to meet the market demand for high energy density batteries. Lithium / sodium metal batteries with lithium / sodium metal as negative electrodes have gradually become a research hotspot due to their high energy density. However, both lithium metal batteries and sodium metal batteries face interface problems caused by factors such as uncontrollable dendrite growth and the resulting safety issues.

[0003] Copper foil and aluminum foil are commonly used as current collectors in lithium metal anodes and sodium metal anodes, respectively. Their inherent lithium / sodium-phobic properties will cause uneven lithium / sodium deposition, which is easy to lead to the formation of lithium / sodium dendrites, and then cause safety problems such as internal short circuits in batteries. Constructing a lithium / sodium-philic layer on the current collector surface is an effective strategy to homogenize lithium deposition.

[0004] Patent CN 112467147 A forms a current collector that inhibits the growth of lithium dendrites by spin-coating an organic solution of a polysulfone polymer on copper foil. Due to the presence of the polar functional group O=S=O, the growth of lithium dendrites is inhibited. However, the polysulfone used is a non-degradable polymer material, which means that polysulfone products are often difficult to recycle after their lifespan ends, which may cause long-term pollution and impact on the environment. In addition, the use of organic solvents NN-dimethylformamide or N-methylpyrrolidone during the experiment not only causes serious harm to the environment, but also directly affects human health. The document "Highly Sodiophilic Heterostructures towards Dendrite-Free Sodium Metal Batteries" designs a heterostructure (V / VO x ), effectively achieving a highly reversible sodium insertion / stripping process and inhibiting the growth of sodium dendrites. However, the operation steps are relatively cumbersome, and the use of strong acids will also cause multiple negative impacts on the environment. Patent CN 108767263A achieves uniform lithium deposition by in-situ growing Zn-MOF two-dimensional nanosheet arrays on copper foil. However, in-situ growth is easily affected by factors such as fluctuations in reaction conditions, environmental factors, substrate surface characteristics, and impurities, and its large-scale application will be subject to certain restrictions. Therefore, the development of a lithium / sodium-philic current collector that is degradable, pollution-free, simply controllable, and easy to scale up is of great market significance. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention proposes a lithium / sodium-philic current collector for lithium / sodium metal batteries and its preparation method and application. The present invention uses natural degradable lignocellulose as raw material and deionized water as dispersant, and simply designs a lithium / sodium-philic layer on copper foil or aluminum foil. The large amount of oxygen-containing functional groups in lignocellulose can effectively regulate the uniform deposition of lithium. When the current collector is used in lithium / sodium metal batteries, it can effectively inhibit the growth of lithium / sodium dendrites.

[0006] To achieve the purpose, the present invention adopts the following technical solution:

[0007] The present invention first provides a lithium / sodium-philic current collector for a lithium / sodium metal battery, comprising: a current collector matrix and a lithium / sodium-philic layer supported on the surface of the current collector matrix, wherein the current collector matrix is ​​a copper foil or an aluminum foil, and the lithium / sodium-philic layer is a wood cellulose layer.

[0008] Furthermore, the surface density of the lithium / sodium-philic layer is 6.4 mg cm -2 ~25.5mg cm -2 , compacted density is 3.2gcm -3 ~6.4 g cm -3 .

[0009] The present application also provides a method for preparing the lithium / sodium-philic current collector for the lithium / sodium metal battery, the specific steps of which are as follows:

[0010] Step 1, add lignocellulose to deionized water, stir magnetically for 0.5-2h at room temperature, pour into a 200-mesh sieve, rinse repeatedly with a large amount of deionized water, and then dry at 60-90°C for 6-12h before use;

[0011] Step 2, adding the lignocellulose treated in step 1 to deionized water, magnetically stirring at room temperature for 0.5-3 hours to obtain a dispersion, pouring it onto the surface of the current collector matrix, and drying it at 60-90° C. for 8-12 hours to form a lithium / sodium-philic layer on the surface of the current collector matrix;

[0012] Step 3: After rolling the current collector in step 2, a lithium / sodium-philic current collector for lithium / sodium metal batteries is finally obtained.

[0013] Furthermore, in step 2, the mass ratio of the lignocellulose to deionized water is 0.5 to 2:80.

[0014] The present invention also provides a lithium / sodium metal battery, comprising the lithium / sodium-philic current collector.

[0015] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0016] 1. The raw material wood cellulose is relatively abundant and cheap. It is biodegradable during production and use and is relatively environmentally friendly.

[0017] 2. Avoid the use of organic solvents and effectively alleviate the environmental pressure caused by the use of organic solvents.

[0018] 3. Simple operation, easy to control experimental variables, suitable for large-scale production.

[0019] 4. It has a wide range of applications and can be used in both lithium metal batteries and sodium metal batteries.

[0020] 5. It can achieve a good homogenization effect on the deposition of lithium / sodium, effectively inhibit the growth of lithium / sodium dendrites, and greatly reduce the safety risks of batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is an optical photograph of the lithium-philic current collector prepared in Example 1.

[0022] Figure 2 This is a scanning electron microscope image of the lithium-philic current collector prepared in Example 1.

[0023] Figure 3 This is a coulombic efficiency diagram of the current collectors of Example 1 and Comparative Example 1 after being assembled into a lithium metal battery.

[0024] Figure 4 This is an optical photograph of the sodium-philic current collector prepared in Example 2.

[0025] Figure 5 This is a coulombic efficiency diagram of the current collectors of Example 2 and Comparative Example 2 after being assembled into a sodium metal battery. DETAILED DESCRIPTION

[0026] The technical solution of the present invention is further described and explained below in conjunction with embodiments, but these embodiments are not intended to limit the protection scope of the present invention.

[0027] 1. Lithium-philic current collectors for lithium metal batteries

[0028] Example 1

[0029] 1. Preparation of current collector:

[0030] Step 1: Add wood cellulose to deionized water, stir magnetically for 30 minutes at room temperature, pour into a 200-mesh sieve, rinse repeatedly with a large amount of deionized water, and dry at 80° C. for 6 hours before use.

[0031] Step 2: Weigh 0.6 g of the wood cellulose treated in step 1 and add it to 80 g of deionized water. Stir magnetically at room temperature for 1 hour. Pour the obtained dispersion onto the surface of the copper foil. After drying at 80° C. for 8 hours, a lithium-philic layer is formed on the surface of the copper foil.

[0032] Step 3: After rolling the current collector in step 2, a lithium-philic current collector for lithium metal batteries is finally obtained. The surface density of the lithium-philic layer is 6.4 mg cm -2 , compacted density is 3.6 g cm -3 .

[0033] 2. Preparation of lithium metal batteries:

[0034] Under the protection of an argon atmosphere glove box, the obtained lithium-philic current collector was matched with lithium metal to assemble into a half-cell. The separator used was a polypropylene separator, and the electrolyte composition was a mixed solution of 1M LiTFSI dissolved in 1,3-dioxolane / ethylene glycol dimethyl ether (volume ratio of 1:1) and 1% wt. LiNO was added. 3 The electrolyte injection volume is 50μL.

[0035] Comparative Example 1

[0036] The difference from Example 1 is that no lignocellulose layer is introduced on the surface of the copper foil substrate, and the bare copper foil is directly used to assemble the lithium metal battery. Specifically, under the protection of an argon atmosphere glove box, the bare copper foil current collector is matched with lithium metal to assemble a half-cell. The diaphragm used is a polypropylene diaphragm, and the electrolyte composition is a mixed solution of 1M LiTFSI dissolved in 1,3-dioxolane / ethylene glycol dimethyl ether (volume ratio of 1:1) and 1% wt. LiNO is added. 3 The electrolyte injection volume is 50μL.

[0037] Morphology characterization and performance testing:

[0038] Figure 1 This is an optical photograph of the lithium-philic current collector prepared in Example 1. Figure 2 This is a scanning electron microscope image of the lithium-philic current collector prepared in Example 1. Figure 1 and Figure 2 The results showed that a lignocellulose-based lithium-philic layer was successfully prepared on the surface of the copper foil substrate.

[0039] Figure 3 The coulombic efficiency diagram of the current collectors of Example 1 and Comparative Example 1 after being assembled into a lithium metal battery. It can be seen that at 0.5 mA cm -2 , 0.5mAh cm -2Under the test conditions, the lithium metal battery based on the lithium-philic current collector can maintain a coulombic efficiency of 98.0% even after 300 cycles, while the coulombic efficiency of the lithium metal battery based on the bare copper foil current collector has decayed seriously after 50 cycles (only 67.6%). This shows that the lithium metal battery based on the bare copper foil current collector has serious lithium dendrite growth and loss of inactive lithium during the cycle process, which leads to the deterioration of the cycle performance of the lithium metal battery. The introduction of the lithium-philic lignocellulose layer can have a better uniform effect on the deposition of lithium and effectively inhibit the growth of lithium dendrites.

[0040] 2. Sodium-philic current collector for sodium metal batteries

[0041] Example 2

[0042] 1. Preparation of current collector:

[0043] Step 1: Add wood cellulose to deionized water, stir magnetically for 30 minutes at room temperature, pour into a 200-mesh sieve, rinse repeatedly with a large amount of deionized water, and dry at 80° C. for 6 hours before use.

[0044] Step 2: Weigh 1 g of the wood cellulose treated in step 1 and add it to 80 g of deionized water. Stir it magnetically at room temperature for 1 hour. Pour the obtained dispersion onto the surface of aluminum foil. After drying at 80° C. for 8 hours, a sodium-philic layer is formed on the surface of the aluminum foil.

[0045] Step 3: After rolling the current collector in step 2, a sodium-philic current collector for sodium metal battery is finally obtained. The surface density of the sodium-philic layer is 12.7 mg cm -2 , compacted density is 4.2 mg cm -3 .

[0046] 2. Preparation of sodium metal batteries:

[0047] Under the protection of an argon atmosphere glove box, the obtained sodium-philic current collector was matched with sodium metal to assemble into a half-cell. The separator used was glass fiber and the electrolyte composition was 1M NaPF 6 Dissolved in diethylene glycol dimethyl ether solvent, and the injection volume of the electrolyte was 110 μL.

[0048] Comparative Example 2

[0049] The difference from Example 2 is that no lignocellulose layer is introduced on the surface of the aluminum foil substrate, and the sodium metal battery is directly assembled with bare aluminum foil. Specifically, under the protection of an argon atmosphere glove box, the bare aluminum foil current collector is matched with sodium metal to assemble into a half-cell. The separator used is glass fiber, and the electrolyte composition is 1M NaPF 6 Dissolved in diethylene glycol dimethyl ether solvent, and the injection volume of the electrolyte was 110 μL.

[0050] Morphology characterization and performance testing:

[0051] Figure 4 This is an optical photograph of the sodium-philic current collector prepared in Example 2. The results show that a lignocellulose-based sodium-philic layer is successfully prepared on the surface of the aluminum foil substrate.

[0052] Figure 5 The coulombic efficiency diagram of the current collectors of Example 2 and Comparative Example 2 after being assembled into a sodium metal battery. It can be seen that at 0.5 mA cm -2 , 0.5mAh cm -2 Under the test conditions, the sodium metal battery based on the sodium-philic current collector can stably cycle 200 cycles and maintain a coulombic efficiency of 97.9%, while the coulombic efficiency of the sodium metal battery based on the bare aluminum foil current collector has decayed seriously (only 62.3%) after 50 cycles. This shows that the sodium metal battery based on the bare aluminum foil current collector has serious sodium dendrite growth and loss of inactive sodium during the cycle process, which leads to the deterioration of the sodium metal battery cycle performance. The introduction of the sodium-philic lignocellulose layer can have a better uniform effect on the deposition of sodium and effectively inhibit the growth of sodium dendrites.

[0053] The above embodiments are only used to explain the present invention, and are intended to illustrate the technical concept and features of the present invention, and do not constitute any limitation to the present invention. For those skilled in the art, changes and modifications can be made according to the spirit of the present invention, and these changes and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A lithium / sodium-philic current collector for a lithium / sodium metal battery, characterized in that: It comprises a current collector matrix and a lithium / sodium-philic layer loaded on the surface of the current collector matrix; wherein the current collector matrix is ​​copper foil or aluminum foil, and the lithium / sodium-philic layer is a wood cellulose layer.

2. The lithium / sodium-philic current collector for lithium / sodium metal batteries according to claim 1, characterized in that: The surface density of the lithium / sodium-philic layer is 6.4 mg cm -2 ~25.5mg cm -2 .

3. The lithium / sodium-philic current collector for lithium / sodium metal batteries according to claim 1, characterized in that: The compacted density of the lithium / sodium-philic layer is 3.2 g cm -3 ~6.4 g cm -3 .

4. A method for preparing a lithium / sodium-philic current collector for a lithium / sodium metal battery according to any one of claims 1 to 3, characterized in that: Here are the steps: Step 1, add lignocellulose to deionized water, stir magnetically for 0.5-2h at room temperature, pour into a 200-mesh sieve, rinse repeatedly with a large amount of deionized water, and then dry at 60-90°C for 6-12h before use; Step 2, adding the lignocellulose treated in step 1 to deionized water, magnetically stirring at room temperature for 0.5-3 hours to obtain a dispersion, pouring it onto the surface of the current collector matrix, and drying it at 60-90° C. for 8-12 hours to form a lithium / sodium-philic layer on the surface of the current collector matrix; Step 3: After rolling the current collector in step 2, a lithium / sodium-philic current collector for lithium / sodium metal batteries is finally obtained.

5. The method for preparing a lithium / sodium-philic current collector for a lithium / sodium metal battery according to claim 4, characterized in that: In step 2, the mass ratio of the wood cellulose to deionized water is 0.5 to 2:

80.

6. A lithium / sodium metal battery, characterized in that: The invention comprises the current collector according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Method for preparing modified lithium cathode copper foil current collector and application thereof

    CN108767263A

  • Anode material for lithium metal battery as well as preparation method and application of anode material

    CN108232117A

  • Copper current collector for lithium metal secondary battery, preparation method thereof and lithium metal secondary battery

    CN108649232A

  • Lithium metal battery negative electrode current collector for inhibiting dendritic crystal growth and modification method thereof

    CN112467147A

  • Sodium metal negative electrode protective layer, sodium metal negative electrode and preparation method and application thereof

    CN112531145A

Cited By

  • Current collector and preparation method and application thereof

    CN120978089A